ASSOCIATION OF THE PRO72ARG (RS1042522) POLYMORPHISM OF THE TP53 GENE WITH THE DEVELOPMENT OF MYELOPROLIFERA-TIVE NEOPLASMS IN THE KHOREZM REGION - Zhumaboeva, Marguba; Boboev, Kodirjon; Matmurodov, Rustambek; Zhumanazarova, Shahzoda (Medical science of Uzbekistan, 2025)
Objective: To evaluate the impact of allele and genotype variants of the Pro72Arg (rs1042522) polymorphism of the TP53 gene on the development of myeloproliferative neoplasms (MPNs). Materials and methods: The study involved 110 patients with clinically and genetically confirmed cases of Рh-positive and Рh-negative MPNs, examining the role of the Pro72Arg (rs1042522) polymorphism of the TP53 gene in the development and prognosis of MPNs. Among them, 34 patients (CML – 26, IP – 7, IT-1) resided in ecologically unfavorable regions of the Khorezm region near the Aral Sea (Group I), and 76 patients (CML – 40, IP – 24, IT – 10, PMF – 2) lived in relatively favorable areas within the Khorezm region (Group II). DNA samples from 105 unrelated healthy individuals of Uzbek ethnicity were used as controls. Results: The results showed that the Pro allele is associated with an increased likelihood of developing diseases, while the high frequency of the Arg allele in the control group suggests a protective effect (χ² = 12.4; p = 0.01). The Pro/Pro genotype was significantly common in patients from unfavorable regions of Xorezm region (χ2=5.6; p=0.03; RR=3.6; 95%CI: 1.05-12.38;), statistical indicators of this genotype indicate its potential association with an increased risk of the disease, the presence of which increases the risk of developing MPN by more than 4 times (OR=4.2; 95%CI:1.27-13.57); whereas the Pro/Arg genotype (χ² = 5.9; p = 0.03) was significantly associated with an increased risk of disease, raising the risk of developing MPNs by more than 2 times (OR = 2.1; 95% CI: 1.15-3.77). The Arg/Arg genotype (χ² = 11.1; p = 0.01), on the other hand, was associated with a protective effect, with its high frequency in the control group confirming its role as a factor that reduces the risk of disease.